THE CONCEPT OF PODCAST PRODUCTION DESIGN "RUANG KITA" AS A MEDIUM OF INSPIRATION FOR MILLENNIALS IN SELF-DEVELOPMENT - Kurniawan, Andreas; Gabriela Bestiadeby; Rinthia Mahardita Istifharin (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
Abstract Ruang Kita” is a program that has been designed with the aim of allowing millennials to enjoy themselves while obtaining a space where they can find self motivation and inspiration in this podcast program which has been packaged with a casual and educative conversation. The “Ruang Kita” podcast consists of 3 episodes. The first episode is titled Becoming a Content Creator for a Better Living which discusses the struggle of Rahel Tama, a college student who is currently building her career as a content creator.Second episode is titled From Passion to Career, which discussed the story of Kelvin Christian who is very passionate about his hobby in the coffee industry.Finally, the last episode is titled Starting a Business Successfully with Best Friend, which discussed the story of two best friends, Mufti and Miqdad in their Betta Fish Business together. This non thesis work uses New Media Theory which explains that the communication message is focused and easy to be channelled through the internet technology and involves the audience to increase the interaction and communication process. “Ruang Kita” will be uploaded to Spotify and Youtube as the main platform.